Studies on vitamin B12 level in fish sauce, fermented fish, soya-bean sauce and serum vitamin B12 level in patients with tropical diseases - Rawadee Thearawibul (Chulalongkorn University, 2014)
Thesis (M.Eng.)--Chulalongkorn University, 1974